An Analytical Study of the General Arts Degree Curricula Offered by Two Selected Universities in Sri Lanka - Kumari, H.M.L. (My University, 2006)
Numerous problems have arisen in regard to relevance of the curricula offered for the Arts Degree Programme in view of the high rate of unemployment among educated persons and particularly among those who have completed their General Arts Degree Programme. Hence an attempt has been made in this study to examine the curriculum of the General Arts Degree Programme. For this purpose, two national universities in Colombo district have been selected as samples. The study has been carried out in association with 226 sample units targeting four aims as outlined below;